Analisis Pelaksanaan Program Makan Bergizi Gratis (MBG) di Sekolah Kec. Palakka Kab. Bone - Sahrul; Saril; Sonia Eka Lestari (Institusi Agama Islam Negeri (IAIN) Bone, 2026)
The Free Nutritious Meal Program (Makan Bergizi Gratis/MBG) is one of the Indonesian government's strategic initiatives to improve the nutritional status of school-age children, reduce stunting, and support the development of high-quality human resources. The successful implementation of this program depends on effective communication, adequate resources, positive implementer commitment, and an appropriate bureaucratic structure. This study aims to analyze the implementation of the Free Nutritious Meal Program in schools located in Palakka District, Bone Regency, and to identify the factors that influence its implementation. This research employed a qualitative field research design using a management approach. Data were collected through observation, interviews, and documentation involving the Head of the Nutrition Fulfillment Service Unit (SPPG) and other relevant informants. The collected data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the MBG program has generally been carried out effectively through coordination between the SPPG and schools in the distribution of nutritious meals. The implementation process reflects the four dimensions of Edward III's policy implementation model, namely communication, resources, disposition, and bureaucratic structure. Nevertheless, several challenges remain, including limited facilities and infrastructure, distribution constraints, logistical management, and the need to strengthen coordination among stakeholders. Therefore, improving institutional capacity, distribution management, and inter-agency collaboration is essential to enhance the effectiveness and sustainability of the MBG program in supporting students' nutritional needs and educational outcomes.